2007
DOI: 10.1093/ietcom/e90-b.9.2219
|View full text |Cite
|
Sign up to set email alerts
|

Basic Study on an Antenna Made of a Transparent Conductive Film

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…However, antennas made up of transparent antennas suffer from low gain as they are made up of AgHT‐8 (silver layer sandwiched between two layers of tin) with conductivity value of 125 000 Siemens/m which is very much less as compared to the copper which has a conductivity value of 5.96 × 10 7 Siemens/m . It is difficult to improve the gain of transparent antennas as the conductive material properties of AgHT need to be changed for increasing the electron mobility for improving the gain which is not in our hand . A technique for increasing the efficiency by the means of soldering where silver was embodied to increase the efficiency by 20% has been proposed in literature .…”
Section: Introductionmentioning
confidence: 99%
“…However, antennas made up of transparent antennas suffer from low gain as they are made up of AgHT‐8 (silver layer sandwiched between two layers of tin) with conductivity value of 125 000 Siemens/m which is very much less as compared to the copper which has a conductivity value of 5.96 × 10 7 Siemens/m . It is difficult to improve the gain of transparent antennas as the conductive material properties of AgHT need to be changed for increasing the electron mobility for improving the gain which is not in our hand . A technique for increasing the efficiency by the means of soldering where silver was embodied to increase the efficiency by 20% has been proposed in literature .…”
Section: Introductionmentioning
confidence: 99%
“…Nessel et al, a NASA engineer revealed wideband, high gain, multilayer Yagi antenna for X band using AgHT‐8. Guan et al designed PIFA and monopole antenna for WLAN applications. Transparent conductive oxide material AgHT‐4 had been used by Katsounaros et al for making UWB antenna followed by designing the transparent antenna for RFID applications .…”
Section: Introductionmentioning
confidence: 99%
“…To get transparency, the previous reported antennas used a rigid glass as a substrate. Recently, to fabricate transparent antennas, transparent indium tin oxide (ITO) and fluorine doped tin oxide (FTO) conductive films are utilized . These films allow transmission of electric currents while provide good optical transparency .…”
Section: Introductionmentioning
confidence: 99%